A Paradigm Shift that Never Was: Justin Lin's New Structural Economics. (1st October 2013) - Fine, Ben; Van Waeyenberge, Elisa
Abstract : This paper assesses the attempt by Justin Lin, former Chief Economist of the World Bank, to posit a new development paradigm through his New Structural Economics, NSE. Lin's attempt to redefine development economics deserves scrutiny for at least two reasons. First, he launched his framework when he was Chief Economist at the Bank. Critical scrutiny of his proposition then allows for continued insights into the complex relationship between scholarship and policy at the Bank. Second, Lin's framework claims a return to a 'structural' understanding of development, with a strong industrial policy rhetoric emanating from it. This has been greeted with considerable enthusiasm by erstwhile critics of the Bank. Closer scrutiny of the NSE, nevertheless, reveals the flawed nature of its core theoretical notion of comparative advantage and exposes its strong, if unfortunately conservative, commitment to a flawed and incoherently applied neoclassical economics, accompanied by a persistently narrow policy scope.